Implications of new legislation (US FSMA) and guidelines (EC) on the establishment of management systems for agricultural water. (October 2018) - Allende, A.; Datta, A.R.; Smith, W.A.; Adonis, R.; MacKay, A.; Adell, A.D.
Abstract: This report summarizes key messages related to agricultural water quality as discussed by an ad hoc panel at the 1st International Symposium of Food Safety in Santiago, Chile. Participating representatives of the academia, industry and government of diverse geographical backgrounds and the audience discussed topics such as (1) implications of the US Food Safety Modernization Act (FSMA:www.fda.gov/Food/GuidanceRegulation/FSMA/ucm277706.htm ) on the Agricultural Water Quality, (2) comparisons between MPN and CFU in analyzing water quality, (3) alternatives to fecal indicator bacteria (FIB) to be used as indicators to evaluate water quality, and (4) vegetative buffers as an alternative to reduce pathogen loads in agricultural surface waters. Panelists identified the following key messages for each topic discussed that are related to agricultural water quality: (1) the FSMA regulation and the new guidance document elaborated by the EC are highly relevant as they provide a definition of agricultural water and specific criteria for different water uses and circumstances; (2) FSMA supports modification from MPN to CFU; (3) Growers require more alternatives for treatment of agricultural water; (4) Vegetative buffers are a potential practical and feasible alternative for agriculture producers to reduce the pathogen and fecal pollution loads of in their agricultural waters. Highlights: FSMA regulation and the EC's guidance document are relevant preventative approaches. FSMA modified the unit used to estimate FIB concentration from MPN to CFU. Growers need more alternatives for treatment of agricultural water. Conferences on food safety need to have a space to discuss practical issues of concern.